A jackknifed difference-based ridge estimator in the partial linear model with correlated errors. Issue 6 (1st November 2016) - Wu, Jibo
ABSTRACT: Tabakan and Akdeniz [Difference-based ridge estimator of parameters in partial linear model. Statist Pap. 2010;51(2):357–368] proposed a difference-based ridge estimator (DBRE) in the partial linear model. In this paper, a new estimator is introduced by jackknifing the DBRE that Tabakan and Akdeniz presented. We investigate the performance of this new estimator over the DBRE and difference-based estimator introduced by Yatchew [An elementary estimator of the partial linear model. Econom Lett. 1997;57:135–143] in terms of mean-squared error and mean-squared error matrix and a numerical example is provided to demonstrate the performance of the estimators.